Study on Preparation and Properties of InN Films on Self-Supporting Diamond Substrates Under Different Nitrogen Flows - Wang, Shuaijie; Qin, Fuwen; Bai, Yizhen; Zhang, Dong (Frontiers in Materials, 2020)
Several InN film samples with superb properties were prepared on a self-supporting diamond substrate for different nitrogen flow rates using an electron cyclotron resonance plasma-enhanced metal-organic chemical vapor deposition (ECR-PEMOCVD) system. After the InN film samples were obtained, the samples were characterized via reflected high-energy electron diffraction (RHEED), X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscope (AFM), and electron probe micro-analysis (EPMA) to study the effect of the nitrogen flow on the quality of the InN films. The experimental results show that the variation in the nitrogen flow has a great impact on the preferential growth of the (0002) crystal plane of the InN thin film. By increasing the nitrogen flow moderately, the crystal quality of the film is improved. Under the growth condition of appropriate nitrogen flow, InN thin films with a preferred orientation along the c-axis can be obtained, and the surface of the resulting InN thin films is relatively flat. However, a high nitrogen flow does not improve the film crystal quality. The results of the experiment and of the analysis show that the InN films prepared with a nitrogen flow rate of 80 sccm have an excellent preferential orientation. The result of the EPMA test shows that the percentages of the In and N atoms in the prepared film samples are close to a ratio of 1:1, and a small amount of metal In droplets is present. In addition, the InN thin films prepared in such condition have an excellent surface morphology and composition.